The Influence of Financial Inclusion, Financial Literacy and Financial Behavior on Company Performance in MSMEs in Makassar City - Wahyuni Saskia; Andi Ainil Putri; Hismawati, Hismawati; A.Muh.Nurjalal; Ishak, Ishak; Linda Razak (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims to analyze the effect of financial inclusion, financial literacy, and financial behavior on company performance in the MSME study in Makassar. Company performance is an achievement (result) obtained through human resources with the division of activities in the form of tasks, roles and responsibilities to achieve company goals. Seeing the potential of micro, small and medium enterprises which are very promising but neglecting financial management is the phenomenon behind this research. This study uses an associative approach. The population and samples are 30 micro, small and medium enterprises in Makassar City. The research data is primary data from respondents which are then analyzed using multiple linear regression techniques. The results of the study using multiple linear regression show that financial inclusion has no significant and positive effect on company performance. Financial literacy has a significant and positive effect on company performance. Financial behavior has no significant effect on company performance.